Deformation analysis of flexural PVA fiber-reinforced RAC slabs. (March 2022) - Yu, Feng; Wang, Hui; Song, Jie; Fang, Yuan; Xu, Bo; Wang, Jingfeng; Shen, Wanyu
Abstract: This paper presents an experimental investigation on flexural performances of PVA fiber-reinforced recycled aggregate concrete (RAC) slabs. Several variable parameters, including span-thickness ratio, reinforcement ratio, content of PVA fiber, replacement rate of recycled coarse aggregate (RCA) are considered. The failure mode of PVA fiber-reinforced RAC slabs is longitudinal reinforcement yielding, concrete crushing and PVA fiber being pulled out or broken along the crack gaps. As RCA replacement rate or span-thickness ratio increases, the reinforcement strain development accelerates and the initial stiffness of slabs decreases, while improving the content of PVA fiber or reinforcement ratio decelerates the reinforcement strain development and increases the initial stiffness of slabs. The displacement ductility coefficient increases as RCA replacement rate or content of PVA fiber increases, while declines as reinforcement ratio or span-thickness ratio enhances. Additionally, considering the impact of RCA replacement rate, a deflection influence coefficient of RCA is introduced, a formula for estimating mid-span deflection of PVA fiber-reinforced RAC slabs is proposed and the predicted results agree well with the experimental data.